2008
DOI: 10.1007/s10694-008-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Findings of the International Road Tunnel Fire Detection Research Project

Abstract: Fire detection systems play a crucial role in ensuring safe evacuation and firefighting operations in road tunnels, but information on the performance of these systems in tunnels has been limited and guidelines for their application in tunnel environments are not fully developed. Recently, the National Research Council of Canada (NRC) and the Fire Protection Research Foundation completed a 2-year international research project, with the support of private-and public-sector organizations, to determine some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The validation efforts included: comparison with full-scale tests conducted specifically for code evaluation, comparison with engineering correlations, comparison with previously published full-scale test data, comparison with standard test, and comparison with documented fire experience. Kashef and Be´nichou [7] and Liu et al [8] have recently validated the use of FDS in assessing the performance of emergency ventilation and detection systems for tunnel applications by extensively comparing the predictions of FDS against field and laboratory experiments. The comparison studies showed that both numerical predictions of FDS and measurements were, in general, in good agreements.…”
mentioning
confidence: 99%
“…The validation efforts included: comparison with full-scale tests conducted specifically for code evaluation, comparison with engineering correlations, comparison with previously published full-scale test data, comparison with standard test, and comparison with documented fire experience. Kashef and Be´nichou [7] and Liu et al [8] have recently validated the use of FDS in assessing the performance of emergency ventilation and detection systems for tunnel applications by extensively comparing the predictions of FDS against field and laboratory experiments. The comparison studies showed that both numerical predictions of FDS and measurements were, in general, in good agreements.…”
mentioning
confidence: 99%
“…As a result, International Road Tunnel Fire Detection Research Project [23] suggested that there are generally three performance criteria for the application of a fire detection system in tunnels. The first criterion is their detection capabilities.…”
Section: Unknown 12%mentioning
confidence: 99%
“…The performance of one flame VID system and two flame/smoke VID systems in road tunnel environments has been investigated in a recent research work [5]. Test results showed that it was challenging for the flame VID system to detect the obstructed fires.…”
Section: Introductionmentioning
confidence: 99%